INCORPORATING DEBATE INTO INQUIRY-BASED TEACHING APPROACH TO IMPROVE THE STUDENTS’ HIGHER-ORDER THINKING SKILLS - Wahyu Budi Riyanda; Wawan Gunawan (Edusentris, 2019)
Since it is believed that individuals with higher-order thinking skills are more welcomed in educational and vocational contexts, teaching them has become a desirable goal in education. For that reason, this study aimed at improving the students’ higher-order thinking skills by incorporating debate in inquiry-based teaching. The study used mixed-methods research design utilizing pre-test and post-test to collect quantitative data and observation checklist to collect qualitative data. The quantitative data were analyzed using a rubrics, while the qualitative data were analyzed using a checklist. The study revealed that the students’ higher-order thinking skills at all levels improved after the treatment. The improvement at Analyze level could be seen from the students’ better organization of information, at Evaluate level, the students showed improvement in seeing problems from various perspectives and at Create level, the students improved in communicating solutions better. Other than that, the improvement was also observed in terms of the students’ speaking ability.